GE_GERICHTE PM/894/2020 vom 12. Mai 2021 - GE Cour de justice (2021)
AUTONOMIE;CONFISCATION(DROIT PÉNAL);COMPETENCE;ALLOCATION AU LÉSÉ;DÉCISION EXÉCUTOIRE;TITRE DE MAINLEVÉE;MAINLEVÉE DÉFINITIVE;DÉCISION ÉTRANGÈRE;CONVENTION DE LUGANO;DÉCLARATION D'EXÉCUTION;ANGLETERRE(ROYAUME-UNI) | CPP.376; CPP.378; CP.73; LP.80; CL